Antisperm antibodies and sperm function in bulls undergoing scrotal insulation. Issue 5 (November 2020) - S Ferrer, Maria; Palomares, Roberto; Hurley, David; Bullington, Anna-Claire; Hoyos-Jaramillo, Alejandro; H Bittar, João
Abstract : Bovine antisperm antibodies (ASAs) have been associated with teratospermia and asthenospermia. It was hypothesized here that scrotal insulation induces the formation of ASAs and deterioration of sperm function. Scrotal insulation bags were placed in 10 bulls for 8 days. Semen was collected on days −29, −22 and −2, twice weekly from days 5 to 54, and thereafter weekly until day 96 (day 0 = first day of scrotal insulation). On each collection day, scrotal circumference, sperm motility, morphology, membrane integrity, acrosome integrity, apoptosis, lipid peroxidation, mitochondrial membrane potential, ASA binding and DNA integrity were evaluated. The percentage of IgG- and IgA-bound sperm increased between days 12 and 96 ( P < 0.0001), in association with poor motility (days 19–30, P < 0.005) and morphology (days 8–40, P < 0.0001). Mean scrotal circumference decreased between days 15 and 75 ( P < 0.0001). There was also a deterioration in sperm membrane integrity (days 19–40, P < 0.0001), acrosome integrity (days 26–89, P < 0.0001), lipid peroxidation (days 5–12, P < 0.0001), and mitochondrial membrane potential (days 12–96, P = 0.001). In contrast, a decrease in apoptotic cells (days 37–83, P = 0.0002) and lipid peroxidation (days 19–96, P < 0.0001) was noticed. Most bulls recovered normospermia by day 96. However, the persistence of ASAs, acrosomal damage and dysfunctional mitochondria suggest a long term effect of scrotal insulation on sperm function and the homeostasis of the reproductive immune system.